The Structure of Discourse-Pragmatic Variation. - Pichler, Heike (Studies in language variation., 2013)
Everyday language use overflows with discourse-pragmatic features. Their frequency, form and function can vary greatly across social groups and change dramatically over time. And yet these features have not figured prominently in studies of language variation and change. The Structure of Discourse-Pragmatic Variation demonstrates the theoretical insights that can be gained into both the structure of synchronic language variation and the interactional mechanisms creating it by subjecting discourse-pragmatic features to systematic variationist analysis. Introducing an innovative methodology that.